Difference sequence spaces and matrix method. (May 2020) - Singh, Sukhdev; Malla, Burhan U Din
Abstract: In this paper, the difference sequence space has been introduced using the infinite matrices. Some particular matrices are used to defined and study the sequence spaces such as the Kothe matrix. The results about the Kothe spaces, Frechet spaces and Banach-Kothe spaces are also discussed in this paper.